Reservoir Characterization of the Paleogene Khurmala Formation in Tawke and Shaqlawa Areas, Kurdistan Region of Iraq - Rzger Abdulla; Hussein Hussein; Masoud Hamad; Alan Abdulla (Iraqi Geological Journal, 2024)
Well logs were utilized to investigate petrophysical properties of the Khurmala Formation’s surface outcrops in Shaqlawa Subdistrict and Tawke Oilfield, e.g., lithology, shale volume, porosity, and fracture. The thickness of the formation is about 15 m in the Shaqlawa section and 42 m in the Tawke Oilfield. Porosity logs were used to estimate porosity; where the porosity values reached a maximum of 52% from the sonic log, 48% from the density log, and 35% from the neutron porosity log. The reservoir quality of the Khurmala Formation, as determined through the analysis of thin sections, which were obtained from outcrop samples, is deemed to be of low quality. The determined shale volume within the examined interval exhibits a moderate level of clay constituents, with the highest gamma-ray measurement indicating a shale content of 29% at some locations within the reservoir. This integrated method using various conventional well logs suggests a great probability of petrophysical properties in the Khurmala Formation to be considered as the reservoir.